2017
DOI: 10.1177/2473011417s000173
|View full text |Cite
|
Sign up to set email alerts
|

The Cavovarus Foot and It’s Association with Fractures of the Fifth Metatarsal

Abstract: Introduction/Purpose: Fifth metatarsal fractures are the most commonly encountered metatarsal fractures. It is often inferred that fifth metatarsal fractures occur at an increased frequency in patients with cavovarus foot position. In particular, zone 2 and zone 3 fractures are thought to be associated with cavovarus feet. However, limited data exists in the literature to support this claim. The hypothesis of this study is that a cavovarus foot alignment is positively correlated with the incidence of fifth met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly, according to other studies, there is a relationship between cavovarus feet and the development of both Jones fractures and stress fractures in the fifth metatarsal. For instance, in their study, "The Cavovarus Foot and Its Association with Fractures of the Fifth Metatarsal," Fuchs et al [ 14 ] noted that patients with acute Jones fractures presented with radiographic hindfoot varus. Some studies have suggested that since Zone 2 and Zone 3 may exhibit similar characteristics, it is not necessary to differentiate between them.…”
Section: Anatomy and Pathophysiology Of Fifth Metatarsal Fracturesmentioning
confidence: 99%
“…Similarly, according to other studies, there is a relationship between cavovarus feet and the development of both Jones fractures and stress fractures in the fifth metatarsal. For instance, in their study, "The Cavovarus Foot and Its Association with Fractures of the Fifth Metatarsal," Fuchs et al [ 14 ] noted that patients with acute Jones fractures presented with radiographic hindfoot varus. Some studies have suggested that since Zone 2 and Zone 3 may exhibit similar characteristics, it is not necessary to differentiate between them.…”
Section: Anatomy and Pathophysiology Of Fifth Metatarsal Fracturesmentioning
confidence: 99%